2017
DOI: 10.2147/ijn.s144777
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the biological risk of functionalized multiwalled carbon nanotubes and functionalized oxygen-doped multiwalled carbon nanotubes as possible toxic, carcinogenic, and embryotoxic agents

Abstract: Carbon nanotubes (CNTs) have been a focus of attention due to their possible applications in medicine, by serving as scaffolds for cell growth and proliferation and improving mesenchymal cell transplantation and engraftment. The emphasis on the benefits of CNTs has been offset by the ample debate on the safety of nanotechnologies. In this study, we determine whether functionalized multiwalled CNTs (fMWCNTs) and functionalized oxygen-doped multiwalled CNTs (fCOxs) have toxic effects on rat mesenchymal stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Moreover, the steps involved in anchoring nanomaterials are much less than the ones reported by Yao et al 28 Cytotoxicity is one of the major concerns when nanoparticles such as AuNPs or CNTs were internalized by MSCs for 24 h or longer. 34,35 A previous study showed that culture medium containing over 32 mg mL À1 CNTs causes toxicity to MSCs aer 6 days of culture, while reducing concentration to 6.4 mg mL À1 showed lower toxicity effect. 36 Another study showed that cellular uptake of AuNPs can cause a dose-dependent cytotoxicity to MSCs.…”
Section: Verication Of Cnt-loaded Mscsmentioning
confidence: 99%
“…Moreover, the steps involved in anchoring nanomaterials are much less than the ones reported by Yao et al 28 Cytotoxicity is one of the major concerns when nanoparticles such as AuNPs or CNTs were internalized by MSCs for 24 h or longer. 34,35 A previous study showed that culture medium containing over 32 mg mL À1 CNTs causes toxicity to MSCs aer 6 days of culture, while reducing concentration to 6.4 mg mL À1 showed lower toxicity effect. 36 Another study showed that cellular uptake of AuNPs can cause a dose-dependent cytotoxicity to MSCs.…”
Section: Verication Of Cnt-loaded Mscsmentioning
confidence: 99%
“…Their basic structure is that of graphite with planes of honeycomb-structured carbon atoms. Carbon black (CB), which is produced from incomplete combustion of heavy petroleum materials under controlled conditions (Apicella et al, 2003), has been widely used in industrial products, such as inkjet printer ink, rubber and plastic products (Lee et al, 2016); electrically conductive plastics (Parant et al, 2017); paints, coatings and cosmetics (Sanders and Peeten, 2011); and so on. CB is a quasi-graphitic form of nearly pure elemental carbon (EC, consists of graphene layers).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible to investigate the role of functional groups in the toxicity of carbon nanomaterials when using CB or engineered carbon particles with different functional groups as model samples of soot particles. Actually, it has been recognized that the surface properties of carbon nanomaterials will influence their biological effects or toxicity (Lara-Martinez et al, 2017;Koromilas et al, 2014). For example, a recent study has found that hydrated graphene oxide exhibited a higher cytotoxicity to THP-1 (a human monocytic leukemia cell line) and BEAS-2B (human bronchial epithelial) cells as a consequence of lipid peroxidation of the surface membrane and membrane lysis compared to pristine and reduced graphene oxide (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible to investigate the role of functional groups in the toxicity of soot when using CB or engineered carbon particles with different functional groups as model sample of soot particles. Actually, it has been recognized that the surface properties of carbon nanomaterials will influence their biological effects or toxicity (Lara-Martinez et al, 2017;Liu et al, 2014b;Koromilas et al, 2014). For example, a recent study has found that hydrated graphene oxide exhibited a higher cytotoxicity to THP-1 and BEAS-2B cells as a consequence of lipid peroxidation of the surface membrane and membrane lysis compared to pristine and reduced graphene oxide (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%